Nanostructured 3D metallic foams for H2O2 electroreduction. (24th August 2016) - Eugénio, S.; Cardoso, D.S.P.; Santos, D.M.F.; Šljukić, B.; Montemor, M.F.
Abstract: Direct borohydride fuel cells, which use sodium borohydride as the fuel, are recently focussing on the use of hydrogen peroxide as oxidant instead of the traditional oxygen gas. Herein we study the electrocatalytic activity of nanostructured 3D Cu-M (M = Fe, Co, Ni) and single metal Ni and Co foams for hydrogen peroxide reduction reaction (HPRR) in alkaline media. The electrode materials are prepared by galvanostatic electrodeposition and their morphology, composition and crystallographic structure are characterised by scanning electron microscopy, energy dispersive X-ray spectroscopy and X-ray diffraction analysis, respectively. The electrochemical characterisation is performed by voltammetry and chronoamperometry measurements, where it is concluded that Cu–Fe and Cu–Ni foams exhibit good catalytic activity for HPRR with a number of electrons transferred during the reaction close to 1. Graphical abstract: Highlights: Nanostructured 3D Co, Ni, and Cu–Fe, Co, Ni foams prepared by galvanostatic deposition. The foams structure, morphology and composition were analysed by SEM/EDXS and XRD. H2 O2 reduction with 0.96 and 1.12 electrons exchanged at Cu–Ni and Cu–Fe electrodes.